2007
DOI: 10.1007/s00428-007-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

PEComas: the past, the present and the future

Abstract: The perivascular epithelioid cell (PEC) is a cell type constantly present in a group of tumors called PEComas. PEC expresses myogenic and melanocytic markers, such as HMB45 and actin. Recently, recurrent chromosomal alterations have been demonstrated in PEC. At present, PEComa is a widely accepted entity. In the past 10 years, the use of this term has allowed to report and describe numerous cases permitting to start highlighting the biology of this group of lesions. PEComas are related to the genetic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
446
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(472 citation statements)
references
References 113 publications
6
446
1
10
Order By: Relevance
“…Common angiomyolipomas typically contain more than one cell type; however, in some tumors one cell type predominates and these angiomyolipomas are consequently named lipoma-like or leiomyoma-like angiomyolipoma. 2 In this study we have demonstrated the constant finding of strong cathepsin K immunoexpression in the spindle and epithelioid smooth muscle-like and adipocyte-like cells in renal angiomyolipoma. Moreover, this finding is according to the previously described role of cathepsin K in adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Common angiomyolipomas typically contain more than one cell type; however, in some tumors one cell type predominates and these angiomyolipomas are consequently named lipoma-like or leiomyoma-like angiomyolipoma. 2 In this study we have demonstrated the constant finding of strong cathepsin K immunoexpression in the spindle and epithelioid smooth muscle-like and adipocyte-like cells in renal angiomyolipoma. Moreover, this finding is according to the previously described role of cathepsin K in adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 52%
“…Angiomyolipoma is the most common mesenchymal neoplasm of the kidney and occurs both sporadically and in patients with tuberous sclerosis, a syndrome caused by losses of tuberous sclerosis 1 (TSC1; 9q34) or tuberous sclerosis 2 (TSC2; 16p13.3) and characterized by mental retardation, seizures and cellular proliferations. 1,2 The pathogenesis of angiomyolipoma is determined by mutations affecting TSC genes, with eventual deregulation of the RHEB/MTOR/ RPS6KB2 pathway. 3 It has been observed that angiomyolipomas regressed somewhat during sirolimus therapy, an MTOR inhibitor, but tended to increase in volume after the therapy was stopped.…”
mentioning
confidence: 99%
“…17,21,22 The PEComa family includes renal and hepatic AMLs, lymphangiomyomatosis, clear cell 'sugar' tumor of the lung, and a group of similar lesions seen at other sites. 23 Cysts and multiple AMLs are the most common renal manifestation in TSC. 24,25 In our series, only three cases (#1, 2, and 16) had other concurrent renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PEComas include angiomyolipoma (AML), lymphangioleiomyomatosis (LAM), clear cell 'sugar' tumour of the lung and extra-pulmonary sites, clear cell myomelanocytic tumour of the falciform ligament/ligamentum teres and rare clear cell tumours of other sites [1].…”
Section: Discussionmentioning
confidence: 99%